Chitosan hydrogels - Yilmaz, E.; Ustürk, Selma; Yilmaz, Osman; Özbilenler, Cahit (Elsevier, 2025)
This chapter covers methods of synthesis, physicochemical properties, and biomedical applications of covalently cross-linked chitosan hydrogels. Covalent chitosan hydrogels have been divided into three categories: hydrogels obtained by cross-linking chitosan with chemical cross-linkers, graft copolymers, and interpenetrating and semi-interpenetrating polymer networks. The chitosan hydrogels derived with the most common cross-linkers, namely, glutaraldehyde, epichlorohydrin, ethylene glycol diglycidyl ether, and genipin, are explored. Specific attention is devoted to the toxicities of the cross-linkers, which is a critical issue in biomaterial design. Injectable, self-healing Schiff-base chitosan hydrogels, smart graft copolymers, and interpenetrating polymer networks based on chitosan have been illustrated with specific examples from the recent literature. The relation of the synthesis method, the type of the cross-linker, and the degree of cross-linking on the physicochemical properties of selected chitosan hydrogels has been scrutinized, and their biomedical relevance has been elucidated. © 2026 Elsevier Inc. All rights reserved..
Keywords: Chemical gel; Chitosan; Dynamic covalent; Dynamic covalent bond; Graft copolymer; Hydrogel; Toxicity